Troxerutin protects against DHT-induced polycystic ovary syndrome in rats - Zixuan Gao; Xiaochen Ma; Jing Liu; Yuhang Ge; Lei Wang; Ping Fu; Zhian Liu; Ruiqin Yao; Xiaonan Yan (BMC, 2020)
Abstract The exact pathogenesis of polycystic ovary syndrome (PCOS), the most common neuroendocrine disorder in women of reproductive age, has not been fully elucidated. Recent studies suggested that chronic inflammation and neurotransmitter disorder involved in the progress of PCOS. Troxerutin, a natural flavonoid, was reported to possess neuroprotective effect in several disease models by inhibiting inflammation or enhancing neurotrophic factor. In this study, we investigated the possible protective effect and mechanism of troxerutin in a dihydrotestosterone (DHT)-induced rat model of PCOS. The PCOS rat models were treated with troxerutin at a dose of 150 mg/kg or 300 mg/kg for up to 4 weeks. Results showed that 300 mg/kg troxerutin significantly decreased the body weight gain and improved the pathological changes of ovary induced by DHT. Meanwhile, the elevated gonadotrophin-releasing hormone (GnRH), gonadotrophin and testosterone in the serum of PCOS rats were reduced with the treatment of troxerutin. The expression of kisspeptin and NKB in arcuate nucleus and their receptors kiss1r and NK3r in GnRH positive neurons of median eminence were markedly decreased in troxerutin-treated rats. Of note, the GnRH inhibitory regulator GABA and stimulatory regulator glutamate were also restored to the normal level by troxerutin. The present study indicated that troxerutin may exhibit a protective effect in PCOS rat model via regulating neurotransmitter release.